Antimicrobial and Mechanical Effects of Zeolite Use in Dental Materials: A Systematic Review - Jessica Hao; Spencer Lang; Francis Mante; Krešimir Pavelić; Fusun Ozer (University of Zagreb. School of Dental Medicine, 2021)
Objective: Ion-incorporated zeolite is a widely used antimicrobial material studied for various dental applications. At present, there is no other systematic review that evaluates the effectiveness of zeolite in all dental materials. The purpose of this study was to review all available literature that analyzed the antimicrobial effects and/or mechanical properties of zeolite as a restorative material in dentistry. Material and methods: Following PRISMA guidelines, an exhaustive search of PubMed, Ovid Medline, Scopus, Embase, and the Dentistry & Oral Sciences Source was conducted. No language or time restrictions were used and the study was conducted from June 1, 2020 to August 17, 2020. Only full text articles were selected that pertained to the usage of zeolite in dental materials including composite resin, bonding agents, cements, restorative root material, cavity base material, prosthesis, implants, and endodontics. Results: At the beginning of the study, 1534 studies were identified, of which 687 duplicate records were excluded. After screening for the title, abstract, and full texts, 35 articles remained and were included in the qualitative synthesis. An Inter-Rater Reliability (IRR) test, which included a percent user agreement and reliability percent, was conducted for each of the 35 articles chosen. Conclusion: Although ion-incorporated zeolite may enhance the antimicrobial properties of dental materials, the mechanical properties of some materials, such as MTA and acrylic resin, may be compromised. Therefore, since the decrease in mechanical properties depends on zeolite concentration in the restorative material, it is generally recommended to add 0.2-2% zeolite by weight.